Contextual Mission Construction according to the Jubata Concept in the Kanayatn Dayak Tribe in Introducing the Triune God - Ceria Ceria; Yunardi Kristian Zega; Fransiskus Irwan Widjaja; Jamin Tanhidy (Asosiasi Ahli Filsafat Keilahian Indonesia, 2022)
The purpose of this research is to describe the contextual mission construction using the concept of Jubata to introducing the concept of the Trinity in a biblical view to Dayak Tanayatn people This study uses a qualitative descriptive approach to identify how the Kanayatn Dayak understand the Jubata figure. The results show that through the adaptative method and using the seven Jubata names in the Kanayatn Dayak language to understanding the concept of the Triune God in biblical view and change the understanding of the survivors' sacrifices to be understood as worldly salvation, not eternal in nature through the image of Jubata (which is equated with the spirit of the ancestors) but is directed to one of God's persons in the Trinity of God the Son (Jesus Christ) as the Savior of mankind. Thus, the contextual mission construction of the Jubata concept in the introduction of the Gospel of the Triune God can be a reference material for carrying out outreach missions to remote tribes and building contextual mission studies that are culturally appropriate to spread the Gospel among the Kanayatn Dayak tribe in Landak, West Kalimantan.